Study of mosquito attractants for photo catalytic mosquito trap - Tristantini, Dewi; -, Slamet; Stephanie, Angela Jessica (International Journal of Engineering and Technology, 2013)
Photo catalytic mosquito trap is made of TiO2-Activated Carbon (AC) with a certain composition of AC. Research concerns on the heat spectrum which is produced by combination process of existing CO2 and humid air. The purpose of performance testing is to observe capability of this device in trapping mosquitoes related to the air temperature profile for heat spectrum is play important role for attracting mosquitoes. Result shows photo catalytic mosquito trap is more effective than devices which only consist of UV light or stream of CO2 and the humid air. A number of mosquitoes trapped by the photo catalyst coated panel configuration and UV lamps were lit proved far more effective because the heat production from recombination process. A little difference in temperature can be detected by mosquito.   Keywords: Photo Catalytic, Mosquito, Recombination.